High Compliance with the 11+ Injury Prevention Program Results in Better Win-Loss Records - Holly Silvers-Granelli; Mario Bizzini; Bert Mandelbaum; Amelia Arundale; Ryan Pohlig; Lynn Snyder-Mackler (International Journal of Sports Physical Therapy)
# Background